Evaluasi Sistem Pengendalian Intern Penjualan Kredit Mega Central Finance Baubau Sulawesi Tenggara - Rafida Bangki, Winti Riyanti, Dian Mayafaty Rauf (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
This research is the result of research that resulted in an internal control system for credit sales at PT. MCF Baubau City, where in the elements of the internal control system of credit sales, namely Organizational Structure, System of Authority and Recording Procedures, Healthy Practices and Quality Employees in accordance with responsibilities. This study has the purpose of finding out the internal control system of credit sales of PT. MCF Baubau City, Southeast Sulawesi. This research is a qualitative research. This study uses interviews, observations and documentation in data collection. The results of this study show that the internal control system of credit sales is inadequate, which can be seen in the procedures that form the internal control system of credit sales, namely a) in the organizational structure, there is no separation of duties and responsibilities in the cash function and credit function where both functions are in the accounting department and b) employees whose quality is in accordance with responsibilities where at the time of acceptance of prospective employees there is no Special requirements are listed to accept new employees and employee training and development have not been implemented.